A field programmable gate array implemented fibre channel switch for big data communication towards smart manufacturing. (June 2019) - Tao, Fei; Tang, Yue; Zou, Xiaofu; Qi, Qinglin
Highlights: An FC switch is designed and implemented on a FPGA at the speed greater than 1 Gbps. FC protocol is adopted to solve data transmission bottleneck in smart manufacturing. FC switch composing 3 modules is applied in a hydrovalve production line. From experiments and comparisons, FC outperforms other data communication approaches. Abstract: With the advances in new-generation information technologies (New IT), such as internet of things (IoT), cloud computing, and big data, etc., the big data-driven smart manufacturing era is coming. The volume of data generated and collected in manufacturing process is explosively growing, and big data need to be transmitted from data resources to a fog or a cloud platform. However, some practical limitations, such as overfull bandwidth, and data loss, confine the promotion of smart manufacturing. The limiting capacity of current data communication technologies becomes the bottleneck for smart manufacturing systems. In this paper, fibre channel (FC) switch based on field programmable gate array (FPGA) is designed and implemented due to its high speed, low latency, and high performance transmission capacities. Categories of comparative experiments were conducted and a case study is presented, which indicate that the designed FC switch meets the need of big data transmission for smart manufacturing. Its advanced capacity of transmitting and processing big data opens a bright perspective for smart manufacturing.